Fatty acid synthase inhibition improves hypertension-induced erectile dysfunction by suppressing oxidative stress and NLRP3 inflammasome-dependent pyroptosis through activating the Nrf2/HO-1 pathway - Luan, Jiaochen; Yu, Mengchi; Gu, Qi; Zhou, Xuan; Shao, Yunqiang; Chen, Tong; Zhang, Jiayi; Zhu, Zheng; Song, Ninghong; Yang, Jie (Frontiers in Immunology, 2025)
BackgroundErectile dysfunction (ED) is a prevalent male sexual disorder, commonly associated with hypertension, though the underlying mechanisms remain poorly understood.ObjectiveThis study aims to explore the role of Fatty acid synthase (Fasn) in hypertension-induced ED and evaluate the therapeutic potential of the Fasn inhibitor C75.Materials and methodsErectile function was assessed by determining the intracavernous pressure/mean arterial pressure (ICP/MAP) ratio, followed by the collection of cavernous tissue for transcriptomic and non-targeted metabolomic analyses. In vitro, a concentration of 10-6 M angiotensin II (Ang II) was applied to rat aortic endothelial cells (RAOECs) to establish a model of hypertension. In vivo, spontaneously hypertensive rats (SHR) were randomly divided into two groups. The SHR+C75 group received intraperitoneal injections of C75 at a dose of 2 mg/kg once a week. After five weeks of treatment, the erectile function of the rats was assessed, and penile tissues were harvested for further analysis. Molecular and protein expression were assessed using Western blotting, qRT-PCR, immunofluorescence staining, and immunohistochemistry.ResultsThe SHR exhibited ED, indicated by reduced maximum ICP/MAP ratios. Histologically, corpus cavernosum tissue of SHR showed elevated fibrosis and endothelial dysfunction. Additionally, increased expression of the NLRP3 inflammasome, Caspase-1, GSDMD, and the pro-inflammatory cytokines IL-1β and IL-18 was observed. Multi-omics analysis revealed significant enrichment in lipid metabolic pathways, with Fasn identified as a hub gene. In vitro, siFasn and C75 enhanced antioxidant markers Nrf2 and HO-1, reduced ROS accumulation, and suppressed NLRP3 and GSDMD levels. In vivo, C75 treatment restored endothelial function and reversed erectile dysfunction, accompanied by decreased oxidative stress and pyroptosis in the penile corpus cavernosum.ConclusionThese findings suggest that Fasn inhibition may offer a promising therapeutic strategy for hypertension-induced ED by alleviating oxidative stress and suppressing NLRP3 inflammasome-dependent endothelial cell pyroptosis via activation of the Nrf2/HO-1 pathway.